Electronic structure, Fermi surface and optical properties of metallic compound Be₈(B₄₈)B₂ - Ali Hussain, Reshak, Prof. Dr. (Elsevier/NORTH-HOLLAND, 2014)
Link to publisher's homepage at http://www.elsevier.com